Macro synthesis of SiC nanopowders via gas-phase reaction initiated by solid-phase reactants vaporizing in combustion synthesis - Fei Li; Jie Zhang; Yiyao Ge; Kexin Chen; Guanghua Liu (Journal of Materials Research and Technology)
SiC nanomaterials exhibit outstanding mechanical properties and multifunctionality due to the size effect. Yet the existing methods fail to provide a low-cost and macro synthesis route for the preparation of high-quality SiC nanopowders. Here we reported a combustion synthesis method for macro synthesis of SiC nanopowders via gas-phase reaction initiated by solid-phase reactants (Na2CO3 and Si powders) vaporizing. The synthesis process is self-sustainable and can prepare over 500g SiC nanopowders at once within a few minutes on the lab equipment. By tuning the reactant stoichiometric ratio and Ar pressure to change the supersaturation of the intermediate gaseous products and control SiC crystal nucleation and growth rates, the controlled preparation of SiC nanopowders has been successfully achieved. We stably prepared SiC nanopowders with the single β phase, a primary particle size <10 nm, narrow size distribution, and a specific surface area >45 m2/g. This study not only achieved significant breakthroughs in the synthesis theory of high-quality SiC nanopowders, but also offered a viable pathway for large-scale industrial applications of SiC nanomaterials.